Sraffa, Leontief, Lange: The political economy of input–output economics - Tiago Camarinha Lopes; Henrique Dantas Neder (EconomiA, 2017)
The fields of Political Economy and Input–Output economics are commonly unrelated due to the discrepancy between the qualitative and quantitative analysis in economic science. With the aim to overcome this separation, this paper relates the basic model of Production of Commodities by Means of Commodities to the paradigm of planning as the substitute for the market by sketching the logical-historical development of Input–Output economics. The model of Sraffa, the Leontief matrices and the Political Economy of Marxist tradition, represented by Oskar Lange, are strongly associated so that the typical qualitative concepts of planning, law of value and historical development of the capitalist system can be connected to the quantitative framework of matrix, programming and mathematical formalization.